Eficácia da gestão de casos nos fatores de risco motores e ambientais de quedas em pessoas idosas caidoras com déficit cognitivo: ensaio clínico randomizado - Candanedo, Maria Juana Beatriz Lima (Universidade Federal de São Carlos, 2023)
Introduction: Falls in the older population are considered a public health problem and their consequences bring physical, psychological and financial losses. It is important to study and evaluate the effectiveness of innovative interventions nationwide on risk factors for falls, in order to contribute to the reduction of occurrences of falls. Objectives: To verify the effectiveness of an intervention based on case management on motor and environmental risk factors for falls in community-dwelling faller older people with cognitive impairment. Methods: This is a randomized study developed in the city of São Carlos- SP, in the year 2021 and 2022. Participants were older people with cognitive deficits and falling from the Multidisciplinary Program of Management Assistance and Management of Falls for Faller Older People (MAGIC). The participants were divided into two groups: Control Group (CG) and Intervention Group (IG). The IG underwent case management for 16 weeks conducted remotely, which involved a multidimensional assessment, explanation of the identified risk factors for falls, completion of intervention proposal based on the identified risks, development of an individualized falls intervention plan, follow-up and review of the plan. There were an initial assessment, a final assessment after 16 weeks, and a follow-up assessment after 6 weeks, remotely. The Short Physical Performance Battery (SPPB), TUG and TUG dual task, Manchester Index, Home Falls and Accidents Screening Tool (HOME FAST) were used, as well as foot inspection and shoe questionnaire. Results: The total sample consisted of 52 older people, 25 from the CG and 27 from the IG. There was no significant interaction between groups and moments. The CG presented a worse performance in muscle strength when compared to the IG, regardless of the assessment. In feet and footwear, there was a significant difference between groups (CG and IG) in the initial assessment and between assessments in both CG and IG. Conclusion: There was no effectiveness of an intervention based on case management on the motor risk factors for falls in faller older people with cognitive impairment. However, regarding environmental risk factors, specifically the use of footwear, it was possible to verify changes regarding the use after the intervention and follow-up, with adherence to the recommendations given. Further randomized clinical trials with the intervention based on case management are suggested to prove the findings.
Effects of case management on motor and environmental risk factors for falls in older fallers with cognitive impairment: a randomized clinical trial
Keywords: Pessoa idosa; Fatores de risco; Força muscular; Quedas; CIENCIAS DA SAUDE